Differential responses of healthy and chronic obstructive pulmonary diseased human bronchial epithelial cells repeatedly exposed to air pollution-derived PM4. (November 2016) - Leclercq, B.; Happillon, M.; Antherieu, S.; Hardy, E.M.; Alleman, L.Y.; Grova, N.; Perdrix, E.; Appenzeller, B.M.; Lo Guidice, J.-M.; Coddeville, P.; Garçon, G.
Abstract: While the knowledge of the underlying mechanisms by which air pollution-derived particulate matter (PM) exerts its harmful health effects is still incomplete, detailed in vitro studies are highly needed. With the aim of getting closer to the human in vivo conditions and better integrating a number of factors related to pre-existing chronic pulmonary inflammatory, we sought to develop primary cultures of normal human bronchial epithelial (NHBE) cells and chronic obstructive pulmonary disease (COPD)-diseased human bronchial epithelial (DHBE) cells, grown at the air-liquid interface. Pan-cytokeratin and MUC5AC immunostaining confirmed the specific cell-types of both these healthy and diseased cell models and showed they are closed to human bronchial epithelia. Thereafter, healthy and diseased cells were repeatedly exposed to air pollution-derived PM4 at the non-cytotoxic concentration of 5 μg/cm 2 . The differences between the oxidative and inflammatory states in non-exposed NHBE and COPD-DHBE cells indicated that diseased cells conserved their specific physiopathological characteristics. Increases in both oxidative damage and cytokine secretion were reported in repeatedly exposed NHBE cells and particularly in COPD-DHBE cells. Diseased cells repeatedly exposed had lower capacities to metabolize the organic chemicals-coated onto the air-pollution-derived PM4, such as benzo[a]pyrene (B[a]P), but showed higher sensibility to the formation of OH-B[a]P DNA adducts, because their diseased state possibly affected their defenses. Differential profiles of epigenetic hallmarks (i.e., global DNA hypomethylation, P16 promoter hypermethylation, telomere length shortening, telomerase activation, and histone H3 modifications) occurred in repeatedly exposed NHBE and particularly in COPD-DHBE cells. Taken together, these results closely supported the highest responsiveness of COPD-DHBE cells to a repeated exposure to air pollution-derived PM4 . The use of these innovative in vitro exposure systems such as NHBE and COPD-DHBE cells could therefore be consider as a very useful and powerful promising tool in the field of the respiratory toxicology, taking into account sensitive individuals. Graphical abstract: Highlights: Innovative in vitro exposure systems to be closer to the human in vivo conditions. Original experimental strategy of repeated exposure to air pollution-derived PM4 . Better knowledge on the adverse effects induced by air pollution-derived PM4 . Highest responsiveness of COPD-DHBE cells exposed to air pollution-derived PM4 . Promising tool in respiratory toxicology taking into account sensitive individuals. Abstract : Usefulness of healthy and diseased human bronchial epithelial cell models to better evaluate the adverse effects induced by repeated exposure to air pollution-derived PM4, considering the sensitive individuals.